Mediastinal monophasic synovial sarcoma with vertebral metastases: A case report - Miaomiao Men; Yousen Wu; Pengqi Tian; Changyou Long; Lei Zhou; Ting Fan (Clinical Case Reports)
Key Clinical Message Mediastinal monophasic synovial sarcoma is a rare subtype that often lacks specific imaging characteristics, posing diagnostic challenges. This case report describes a mediastinal monophasic synovial sarcoma with vertebral metastasis, emphasizing imaging findings, differential diagnosis, and pathological features, thereby providing crucial support for accurate diagnosis and treatment planning.